Pembelajaran Matematika Pada Kelas 3 SD Di SD N 101765 - Lailatun Nur Kamalia Siregar; Suci Pitri Yana; Ikhrawati Suryani; Dwi Haryati; Satria Hutabarat; Dea Azka Nadira; Taufik Hidayat Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses materials for the mathematics learning process at SD 101765. Thus, this article was created by discussing the mathematics learning process using media, as one of the learning components used. This research uses research data directly, through research by researchers. This research uses a literature study method. This research aims to discuss the learning process at SD 1101765 in Bandar Loyal. The results of this research are that media is a means of disseminating learning information, including in the field of mathematics